Gambaran Penggunaan Obat Hipertensi pada Pasien Rawat Jalan di Puskesmas X Kabupaten Tanah Laut Kalimantan Selatan - Karunita Ika Astuti; Uswatun Rahimah; Depy Oktapian Akbar (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Hypertension is one of the causes of early death when a concern all over the world which killed 8 million worldwide and almost 1.5 million people per year in the Southeast Asia region. The problem of hypertension will continue to develop if it is not handled properly it is estimated that 1.56 billion adults will be affected by hypertension in 2025. The purpose of this study is to find out the description of the use of hypertension drugs in one of Puskesmas in Tanah Laut from April to May 2019. This research was carried out observational with a cross sectional approach to 300 samples. Based on the gendre of the 300 prescriptions most women were 230 (77%) cases compared to men 70 (23%), the most prescribed drugs were in the age group 46-55 years had the largest number as hypertension sufferers with a percentage of 44 % or 132 patients, nifedipin (61%) 2,669 tablets and the number of patients 148 people (49%).